PERHITUNGAN KEBUTUHAN PEMBESIAN ABUTMENT PADA PEMBANGUNAN JEMBATAN CIHIEUM KECAMATAN LEMAHSUGIH KABUPATEN MAJALENGKA - Pradana, Rana; Kholiq, Abdul (Universitas Majalengka, 2019)
In Engineering. Abutment refers to the substructures rests or contacts. Single-Spanbridge have abutments at each end which vertical provide and lateral support for the bridge, as well as acting as retaining walls to resist lateral movement on the earthen fill of the bridge approach. On the process, contractor should be able in calculating how much material needed to make effective and effisien process. Planned abutment has 8.20m in height and 7 meter wide without central pier.